Chlorine Gas Inhalation: Human Clinical Evidence of Toxicity and Experience in Animal Models - White, Carl W. (American Thoracic Society, 2010)
Humans can come into contact with chlorine gas during short-term, high-level exposures due to traffic or rail accidents, spills, or other disasters. By contrast, workplace and public (swimming pools, etc.) exposures are more frequently long-term, low-level exposures, occasionally punctuated by unintentional transient increases. Acute exposures can result in symptoms of acute airway obstruction including wheezing, cough, chest tightness, and/or dyspnea. These findings are fairly nonspecific, and might be present after exposures to a number of inhaled chemical irritants. Clinical signs, including hypoxemia, wheezes, rales, and/or abnormal chest radiographs may be present. More severely affected individuals may suffer acute lung injury (ALI) and/or acute respiratory distress syndrome (ARDS). Up to 1% of exposed individuals die. Humidified oxygen and inhaled β-adrenergic agents are appropriate therapies for victims with respiratory symptoms while assessments are underway. Inhaled bicarbonate and systemic or inhaled glucocorticoids also have been reported anecdotally to be beneficial. Chronic sequelae may include increased airways reactivity, which tends to diminish over time. Airways hyperreactivity may be more of a problem among those survivors that are older, have smoked, and/or have pre-existing chronic lung disease. Individuals suffering from irritant-induced asthma (IIA) due to workplace exposures to chlorine also tend to have similar characteristics, such as airways hyperresponsiveness to methacholine, and to be older and to have smoked. Other workplace studies, however, have indicated that workers exposed to chlorine dioxide/sulfur dioxide have tended to have increased risk for chronic bronchitis and/or recurrent wheezing attacks (one or more episodes) but not asthma, while those exposed to ozone have a greater incidence of asthma. Specific biomarkers for acute and chronic exposures to chlorine gas are currently lacking. Animal models for chlorine gas inhalation have demonstrated evidence of oxidative injury and inflammation. Early epithelial injury, airways hyperresponsiveness, and airway remodeling, likely diminishing over time, have been shown. As in humans, ALI/ARDS can occur, becoming more likely when the upper airways are bypassed. Inhalation models of chlorine toxicity provide unique opportunities for testing potential pharmacologic rescue agents.